Swaps and Other Derivatives. - Flavell, Richard R. (John Wiley & Sons, 2011)
"Richard Flavell has a strong theoretical perspective on swaps with considerable practical experience in the actual trading of these instruments. This rare combination makes this welcome updated second edition a useful reference work for market practitioners."--Satyajit Das, author of Swaps and Financial Derivatives Library and Traders and Guns & Money: Knowns and Unknowns in the Dazzling World of DerivativesFully revised and updated from the first edition, Swaps and Other Derivatives, Second Edition, provides a practical explanation of the pricing and evaluation of swaps and interest rate deri.